Synthetic strategies to access silacycles - Chen, Fengjuan; Liu, Luo; Zeng, Wei (Frontiers in Chemistry, 2023)
Comparison with all-carbon parent compounds, the incorporation of Si-element into carboskeletons generally endows the corresponding sila-analogues with unique biological activity and physical-chemical properties. Silacycles have recently shown promising application potential in biological chemistry, pharmaceuticals industry and material chemistry. Therefore, the development of efficient methodology to assemble versatile silacycles has aroused increasing concerns in the past decades. In this review, recent advances in the synthesis of silacycle-system are briefly summarized, including transition metal-catalytic and photocatalytic strategies by employing arylsilanes, alkylsilane, vinylsilane, hydrosilanes, and alkynylsilanes as starting materials. Moreover, a clear presentation and understanding of the mechanistic aspects and features of these developed reaction methodologies have been high-lighted.